Prevalence and factors associated with burnout among nurses in Jeddah: a single-institution cross-sectional study - Jumanah T. Qedair; Renad Balubaid; Raghad Almadani; Suzana Ezzi; Tarteel Qumosani; Rania Zahid; Turki Alfayea (BMC, 2022)
Abstract Background Health care workers, especially nurses, experience significantly elevated levels of emotional and social stressors in the work environment. Therefore, nurses develop high levels of burnout as the stress persists for prolonged periods. The main purpose of this paper is to measure burnout levels amongst nurses and find a relation between burnout levels and demographic factors. Methods This descriptive cross-sectional study was held from the 23rd of May till the 6th of September 2021 in King Abdulaziz Medical City of National Guard Health Affairs (KAMC-JD) in Jeddah. Data had been collected voluntarily from the nurses through electronic surveys that included demographic data and the Maslach Burnout Inventory (MBI) that measures three dimensions of burnout which are emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA). The association between demographic variables and burnout had been studied using the Fisher Exact test and binary logistic regression. Results Out of the 1300 nurses working in KAMC-JD, 250 completed the survey. Burnout had been detected in 112 nurses (44.8%). Out of the 250 nurses, 26.4% were found to be at a high risk of burnout, which means they have high or moderate scores of EE and DP, with low ones in PA. The majority of the participants had high burnout levels in each of burnout components, and 99.6% of them scored high in at least one of the three dimensions. Level of burnout was significantly correlated to certain demographic factors which were the nationality (p-value = 0.01) and working unit (p-value = 0.02). On the other hand, there was no significant association between burnout and age, gender, or marital status. Conclusion This study proves that a high percentage of nurses fell victims to burnout with a strong association between certain demographic data namely nationality as well as working unit and burnout levels. Taking into consideration the negative impact of burnout on both nurses and patients, conducting more studies about burnout among nurses, its effect on them, and the risk factors behind it is needed. Early treatment and management are also recommended to avoid the undesirable outcomes.